PERAN GURU DALAM PEMBELAJARAN DAN PENANGANAN PERILAKU ANAK AUTISME DI LEMBAGA BIMBINGAN BELAJAR BERKEBUTUHAN KHUSUS WIDYA WICARA - Rahma Aulia; Yahdinil Firda Nadirah (STKIP Subang, 2026)
This study aims to describe the role of teachers in the learning process and handling the behavior of autistic children at the Widya Wicara Special Needs Tutoring Institute for Children with Special Needs. The method used is descriptive qualitative through interviews and direct observation of teachers and children's learning activities. The results of the study indicate that teachers have a crucial role in developing children's independence through structured learning, basic skills training, and the use of visual media appropriate to the characteristics of autistic children. Teachers also apply a gentle and empathetic approach in handling tantrums or emotional outbursts, such as providing comfort, diversion, and providing positive stimuli. In addition, the social and interaction skills of autistic children are gradually trained through intensive mentoring. The research findings indicate developments in children's cognitive, social, and emotional regulation abilities after consistent learning. Parental support is an important factor in strengthening the results of the intervention. Overall, the directed role of teachers and the use of appropriate learning strategies contribute significantly to the development of autistic children in special education environments.